Meta-Analysis the Effect of Nicotine Replacement Therapy on the Successful Smoking Cessation - Lina Eta Safitri; Agus Kristiyanto; Bhisma Murti (Journal of Epidemiology and Public Health, 2021)
Background: About 23% of the world's population smokes, which includes 32% of men with the highest prevalence coming from Indonesia and 7% are women. East Asia and Southeast Asia have the highest smoking prevalence in the world at around 45%, while in Indonesia, the problem of smoking is a serious threat due to the increasing prevalence of smoking at 18 years of age from 7.2% to 9.1%. This study aims to analyze the magnitude of the effect of using NRT on the success of smoking cessation based on a number of previous similar studies. Subjects and Method: This research is a systematic review and meta-analysis carried out by following the PRISMA flow diagram. The process of searching for articles through a journal database which includes: Google Scholar, PubMed, and Science Direct by selecting articles published in 2011-2020. Keywords used include: "nicotine replacement therapy" AND "smoker" OR "smoking" AND "smoking cessation". The inclusion criteria were a full paper article with an observational study design, English and Indonesian, and analyzed using multivariate analysis with adjusted odds ratio. Articles that meet the requirements were analyzed using the Revman 5.3 application. Results: Nine articles were reviewed in this study with a cohort study design. A meta-analysis of nine cohort studies showed that use of nicotine replacement therapy was 1.42-fold increased smoking cessation success compared to placebo (aOR 1.42; 95% CI 1.14 to 1.76; p <0.002). Conclusion: Nicotine replacement therapy improves smoking cessation success.